Anharmonic correlated einstein model for Xafs cumulant of orthorhombic crystal with impurity - Nguyen, Hung Van; Nguyen, Hung Ba (VNU Journal of Science: Mathematics - Physics; Vol 20 No 3AP, 2017)
Abstracts